Analysing the effects of healthcare payment policies in conjunctionwith tax - benefit policies: A microsimulation study with real - world healthcare data - Aaltonen Katri; Tervola Jussi; Heino Pekka (Turun yliopisto, 2022)
In Europe, many people experience financial hardship due to healthcare payments despite (near-)universal healthcare systems. In Finland, as well as in many other countries, austerity has further widened the gaps in coverage through increases in patient payments. However, the distributional analyses of austerity have concentrated on the effects of tax benefit policies alone. We present a method for examining how health payment policies and tax-benefit policies affect household incomes in conjunction, to evaluate the total effect of implemented and planned policies. We linked the national tax-benefit microsimulation model, SISU, and its nationally representative 15% sample of households in Finland in 2017 (n=826,001) with administrative real-world healthcare data (Finnish Institute for Health and Welfare Care Register for Health Care, HILMO; and Social Insurance Institution of Finland, Kela, National Health Insurance reimbursement registers). As a case example, we analysed the effects on relative poverty risk and poverty gap during two government terms. We found that between 2011 and 2015, tax-benefit policies contributed to decreasing relative poverty, and health payment changes had no measurable effects. In 2015–2019, the poverty risk rate and average gap increased due to tax-benefit policies, and health payment changes strengthened the effects by 10% to 20%. Health payments, and their increases, mainly deteriorated the position of older adults; nevertheless, their poverty risk mostly remained below the population average. Social assistance had an important buffering effect among under 65-year-old population. Health payment increases thus exacerbated the effects of austerity on the oldest age-groups, who, based on tax-benefit analyses alone, were relatively well protected.